Visible Light-promoted Preparation of 2,3-Dihydrobenzofurans and Coumaranones - Wu, Ting-Ting; Wang, Wengui (Current Organic Chemistry, 2024)
2,3-Dihydrobenzofuran and coumaranone are readily available in numerous naturally occurring compounds. They mostly exist in plenty of food plants and medicinal plants. Such compounds constitute a series of flavor components and bioactive molecules. Their preparation has been an attractive field of research. In the past few decades, great efforts have been made in the preparation of the 2,3-dihydrobenzofuran structure through both metal-catalyzed and organocatalyzed ways. Visible light-promoted reactions sprang up in the early 21st century and represent a green manner of transformations. Under the irradiation of visible light, radicals could be generated under milder conditions. Thus, visible lightpromoted reactions spread widely in the field of chemical synthesis. In recent years, visible light-promoted preparation of 2,3-dihydrobenzofuran and coumaranone has been developed by different groups, including both intramolecular and intermolecular reactions. The benign reaction conditions allow better functional group-tolerance and lead to diverse structures. Several reviews on the synthesis of 2,3- dihydrobenzofuran have been reported. However, visible light-promoted approaches to such structures have not been well reviewed. Our review will cover the literature that has been reported on the discovery of 2,3- dihydrobenzofuran in food and visible light-promoted preparation of 2,3-dihydrobenzofuran, attempting to summarize the existing methods and provide guidance to the chemists on the present challenges.
Keywords: dearomatization